Perspektif Sifat ‘Ajuula dalam Al-Qur’an Menurut Ibnu Katsir - Wisqa, Urwatul (Lembaga Yasin AlSys, 2023)
Ajuula or what is commonly called haste. Haste is to look for something or choose it before the time comes according to lust, and this is usually based on lust. So there is the expression